The need for nutritional assessment and interventions based on the prognostic nutritional index for patients with femoral fractures: a retrospective study - Miao He; Qinghong Fan; Yuhang Zhu; Dexing Liu; Xingxing Liu; Shan Xu; Jiachen Peng; Zhaoqiong Zhu (Perioperative Medicine, 2021)
Abstract Background The incidence of adverse perioperative outcomes in surgery for femoral fractures is high and associated with malnutrition. Here, we identified independent factors and assessed the predictive value of the prognostic nutritional index (PNI) for perioperative adverse outcomes in patients with femoral fractures. Methods This retrospective study included 343 patients who underwent surgery for a single femur fracture. Demographic characteristics, surgery and anaesthesia records and blood test results at admission, 1 day postoperatively and before discharge were evaluated using logistic regression analysis. The discriminatory ability of the independent factors was assessed using the receiver operating characteristic curve analysis, and DeLong’s test was used to compare the area under the curve (AUC). Results Overall, 159 patients (46.4%) experienced adverse perioperative outcomes. Amongst these, 123 (35.9%) had lower limb vein thrombus, 68 (19.8%) had hospital-acquired pneumonia, 6 (1.7%) were transferred to the postoperative intensive care unit, 4 (1.2%) had pulmonary embolism, 3 (0.9%) died during hospitalisation and 9 (2.6%) had other adverse outcomes, including incision disunion, renal and liver function impairment, acute heart failure, acute cerebral infarction and stress gastroenteritis. The PNI at admission, age, postoperative hospital stay, time to admission, hypertension, combined injures and surgery type were independent factors for adverse perioperative outcomes. Based on the AUC (PNI at admission: 0.772 [0.723–0.821], P < 0.001; age: 0.678 [0.622–0.734], P < 0.001; postoperative hospital stay: 0.608 [0.548–0.668], P = 0.001; time to admission: 0.585 [0.525–0.646], P = 0.006), the PNI at admission had optimal discrimination ability, indicating its superiority over other independent factors (age vs. PNI at admission, P = 0.002; postoperative hospital stay vs. PNI at admission, P < 0.001; time to admission vs. PNI at admission, P < 0.001). Conclusions Patients with femoral fractures require a nutritional assessment and appropriate nutritional intervention at admission, and that the PNI value at admission may be a good nutritional assessment indicator.